1981
DOI: 10.1901/jeab.1981.35-55
|View full text |Cite
|
Sign up to set email alerts
|

An Interresponse Time Analysis of Variable‐ratio Punishment

Abstract: An interresponse time analysis was used to study the effects of variable-ratio punishment schedules on the temporal pattern of reinforced responding. Twelve pigeons responded on a baseline variable-interval schedule of food reinforcement. A variable-ratio ten schedule of electric shock punishment was then introduced. The shock intensity was systematically increased to the highest intensity at which responding could be maintained. At this intensity, the mean variable-ratio value was increased and then decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 33 publications
3
14
2
Order By: Relevance
“…When absolute response rates are low, small increases or decreases translate into large differences in relative rates. Unlike previous research (e.g., Appel, 1968;Filby & Appel, 1966;Galbicka & Branch, 1981;Lande, 1981;Sizemore & Maxwell, 1985), shock intensity did not affect IRT distributions or response rates, and there was no interaction between shock intensity and the range of IRTs eligible for shock. This may be because the shock duration was too brief, the no-shock baseline strengthened responding, or shock intensity was manipulated across phases.…”
Section: Phasecontrasting
confidence: 88%
See 4 more Smart Citations
“…When absolute response rates are low, small increases or decreases translate into large differences in relative rates. Unlike previous research (e.g., Appel, 1968;Filby & Appel, 1966;Galbicka & Branch, 1981;Lande, 1981;Sizemore & Maxwell, 1985), shock intensity did not affect IRT distributions or response rates, and there was no interaction between shock intensity and the range of IRTs eligible for shock. This may be because the shock duration was too brief, the no-shock baseline strengthened responding, or shock intensity was manipulated across phases.…”
Section: Phasecontrasting
confidence: 88%
“…For example, Filby and Appel reported that 0.2‐mA and 0.4‐mA shocks increased response rates, but shock intensities of 0.6 mA and higher decreased response rates. Similar results were reported by Appel (1968), Arbuckle and Lattal (1992), Lande (1981), and Sizemore and Maxwell (1985).…”
supporting
confidence: 90%
See 3 more Smart Citations